ENGLISH TOURISM AT TANGKENO AS A TOURISM VILLAGE - R. Roslina (Journal of English Education, 2016)
This community service program is aimed to improve the ability of Tangkeno youth in serving foreign visitor by using English. This is done due to the examine of the problems commonly faced by the Tangkeno in serving foreign visitor namely: (1) guiding services are still performed by external parties; (2) alternative tourist spots tend to be not visited by visitors who come without a guide, it is caused by the absence of a local guide who can direct visitors to that alternatives spot; and (3) although some residents have been delegated to learn English intensively in  Pare, East Java, but they have not been able to serve up to guests.This community service program includes four phases of activities, namely: ((1) preparation, preparation of curriculum and syllabus of learning English Tourism; (2) the determination of the participants; (3) the English tourism training; (4) practice/micro guiding English; and (5 ) writing report. Furthermore, the method used in the training and mentoring include: (1) participatory methods, (2) focus group discussions (FGD) (3) division of the working group (4) practice and training in the classroom, (5) Analysts need. Finally, the resulting output are as follow (1) a local guide in the village Tangkeno; (2) MoU Government of Bombana and Nineteen Universitas Sembilanbelas November Kolaka; and (3) Scientific Publications